K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

sửa lại : \(\frac{16}{15}\cdot\frac{17}{16}\cdot\frac{18}{17}\cdot...\cdot\frac{2010}{2009}\cdot\frac{2011}{2010}\)

\(=\frac{16\cdot17\cdot18\cdot...\cdot2010\cdot2011}{15\cdot16\cdot17\cdot...\cdot2009\cdot2010}\)

\(=\frac{2011}{15}\)

22 tháng 9 2018

a,

\(\frac{45}{46}>\frac{2011}{2012}\)

b,

\(\frac{2010}{2011}< \frac{17}{16}\)

Hok tốt!

22 tháng 9 2018

\(a,\frac{45}{46}\)và \(\frac{2011}{2012}\)

Ta có: \(1-\frac{45}{46}=\frac{1}{46};1-\frac{2011}{2012}=\frac{1}{2012}\)

\(\frac{1}{46}>\frac{1}{2012}\Rightarrow\frac{45}{46}>\frac{2011}{2012}\)

\(b,\frac{2010}{2011}\)và \(\frac{17}{16}\)

Ta có: \(\frac{2010}{2011}< 1;\frac{17}{16}>1\Rightarrow\frac{2010}{2011}< \frac{17}{16}\)

9 tháng 9 2016

a) \(1=\frac{45}{46}+\frac{1}{46}\)

    \(1=\frac{2011}{2012}+\frac{1}{2012}\)

\(\frac{1}{46}>\frac{1}{2012}\)\(\Rightarrow\)\(\frac{45}{46}< \frac{2011}{2012}\)

b)Vì 2010/2011 < 1 và 17/16 > 1 => 2010/2011 < 17/16

20 tháng 9 2015

\(=\frac{16}{15}\times\frac{17}{16}\times\frac{18}{17}\times...\times\frac{2010}{2009}\times\frac{2011}{2010}\)

\(=\frac{1}{15}\times2011\)

\(=\frac{2011}{15}\)

4 tháng 7 2017

\(\frac{1}{15}x1\frac{1}{16}x1\frac{1}{17}x...x1\frac{1}{2009}x1\frac{1}{2010}=\frac{1}{15}x\frac{17}{16}x\frac{18}{17}x...x\frac{2010}{2009}x\frac{2011}{2010}=\frac{2011}{240}\)

11 tháng 2 2019

bài 1:

1 - 2007/2008= 1/2008

1- 2009/2010= 1/2010

1/ 2008 > 1/2010

nên 2007/ 2008 < 2009/2010

k mk nha

A = \(\dfrac{2008}{2009+2010+2011}+\dfrac{2009}{2009+2010+2011}+\dfrac{2010}{2009+2010+2011}\)

Ta có: 

\(\dfrac{2008}{2009}>\dfrac{2008}{2009+2010+2011}\)

\(\dfrac{2009}{2010}>\dfrac{2009}{2009+2010+2011}\)

\(\dfrac{2010}{2011}>\dfrac{2010}{2009+2010+2011}\)

Từ 3 điều trên suy ra : A < B

13 tháng 7 2020

Trả lời:

\(\frac{2011\times2010-1}{2009\times2011+2010}\)

\(=\frac{2011\times\left(2009+1\right)-1}{2009\times2011+2010}\)

\(=\frac{2009\times2011+2011-1}{2009\times2011+2010}\)

\(=\frac{2009\times2011+2010}{2009\times2011+2010}\)

\(=1\)

13 tháng 7 2020

\(\frac{2011\times2010-1}{2009\times2011+2010}\)

\(=\frac{2011\times2010-1}{2009\times2011+2011-1}\)

\(=\frac{2011\times2010-1}{2010\times2011-1}\)

\(=1\)